PENYUSUNAN RANCANGAN KOMPETENSI TEKNIS DEPARTEMEN HUMAN RESOURCES PADA PT X - Renata Ivana Ryantandi (Business Administration Department - Universitas Katolik Parahyangan, 2022)
Technical competency is a supporting factor in carrying out certain types of work. Competency is usually applied in competency-based human resources management. In this study, research was conducted on companies engaged in the Automotive Industry, in the company it was found that Human Resource management was less than optimal in carrying out its functions.The purpose of this research is to design technical competencies for the Human Resources Department, preceded by knowing the process of designing technical competencies in the Human Resources Department and knowing what technical competencies must be in the Human Resources Department. This type of research is qualitative, with a case study method. The data collection technique is interviews with three people from the Human Resources Department and is also supported with relevant secondary data from the company. The result of this research is the design of technical competence for the Human Resources Department which consists of 30 technical competencies with standard level starting from level 0 to 3. The recommendation that can be given is that the Human Resources Department should be able to implement this design and develop it for the whole company.